1989
DOI: 10.1177/036354658901700403
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional dynamic motion analysis of the anterior cruciate ligament deficient knee joint

Abstract: Dynamic three-dimensional motion analyses of 15 fresh human knee joints subjected to combinations of flexion velocity and moment, internal and external femoral torque, and horizontal shear before and after sectioning the ACL were performed. ACL deficient specimens demonstrated marked anterior instability without rotational instability. The pivot shift phenomenon occurred with an isolated ACL deficiency and was the result of anterior instability. The pivot shift was accentuated by external femoral torque, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 12 publications
2
32
2
Order By: Relevance
“…It is not clear how the envelope of movement corresponds to the function of the knee, because the added loading conditions during weight-bearing could not be included in this study. Cadaver experiments by Lane et al 10 and Reuben et al 11 showed no difference with quadriceps load in the envelope of tibial rotation before and after division of the ACL. This may suggest that the effect of loading the quadriceps is to stabilise the knee.…”
Section: Figmentioning
confidence: 92%
“…It is not clear how the envelope of movement corresponds to the function of the knee, because the added loading conditions during weight-bearing could not be included in this study. Cadaver experiments by Lane et al 10 and Reuben et al 11 showed no difference with quadriceps load in the envelope of tibial rotation before and after division of the ACL. This may suggest that the effect of loading the quadriceps is to stabilise the knee.…”
Section: Figmentioning
confidence: 92%
“…As the knee flexes, there is a posterior displacement of the femoral-tibial contact location, primarily on the lateral side. 8,23,44,53 This displacement is thought to increase the lever arm of the quadriceps, thereby improving its efficiency in activities such as stair climbing and rising from a chair. 4 Conversely, when the knee extends, the contact point moves anteriorly and the lever arm of the posterior muscles increases.…”
Section: Future Researchmentioning
confidence: 99%
“…These differences though were typically small though statistically significant; Wroble et al (1993) concluded their results were "clinically unimportant". However other transection studies in cadaver knees have not shown an increase in internal rotation range (Lane et al, 1994;Reuben et al, 1989;Wünschel et al, 2010), and Lo et al (2008) showed no increase in ACL force on internal rotation in vitro. In an in vivo study, Hemmerich and colleagues (2011) found that ACL-deficient patients showed an increase in internal rotation range, but at 0° flexion and not at 30°.…”
Section: Internal Rotationmentioning
confidence: 76%
“…Ligament strain (Ahmed et al, 1987;Bach & Hull, 1998;Berns et al, 1992;Beynnon et al, 1992;Beynnon et al, 1997;Fleming et al, 2001;Gabriel et al, 2004;Sakane et al, 1997;Takai et al, 1993;Torzilli et al, 1994) or load Markolf et al, 1995) increases with an anterior force on the tibia. When the ACL is cut anterior translation increases (Diermann et al, 2009;Fukubayashi et al, 1982;Hsieh & Walker, 1976;Markolf et al, 1976;Oh et al, 2011;Reuben et al, 1989;Wroble et al, 1993;Yoo et al, 2005;Zantop et al, 2007), or a given translation is resisted by a lesser force (Butler et al, 1980;Li et al, 1999;Lo et al, 2008;. And while the function of the whole ligament is beyond question here, that of the two bands is another matter.…”
Section: Anterior Translationmentioning
confidence: 99%